Structured Physiotherapy Outperforms Traditional Massage for Managing Postpartum Neck Pain in Working Mothers: A Clinical Investigation - Negi, Nidhi; khan, Jafar; Pal, Renuka; Annamalai, KM.; Goyal, Smita Barya; Jain, Vardhman; Hirendra Rai, Richa; Qureshi, Abid R; Jain, Preksha; Kania, Vaishnavi (Journal of Neonatal Surgery, 2025)
Background: Cervical discomfort is a common issue among postpartum women, particularly those returning to desk-based work. This study investigates and compares the outcomes of structured physiotherapy exercises and traditional midwife massage in managing neck pain among lactating working mothers. Methods: A total of 30 lactating women aged 18–40 years, experiencing neck pain, were enrolled in a randomized controlled trial lasting 12 weeks. They were evenly assigned into two groups (n=15 each). Group A received traditional massage therapy administered by midwives, while Group B followed a prescribed physiotherapy exercise protocol. Assessments using the Neck Disability Index (NDI) and Shoulder Pain and Disability Index (SPADI) were conducted at the start and at 15-day intervals. Independent t-tests were used for statistical evaluation. Results: Both treatment groups showed improvement; however, Group B exhibited significantly greater reductions in NDI and SPADI scores, especially by Day 61–90 (p<0.001). SPADI scores in Group B decreased from 105.53 to 22.87, and NDI scores from 44.93 to 4.07. Conclusion: Structured physiotherapy demonstrated superior efficacy over traditional massage in alleviating neck and shoulder pain and disability in lactating women with desk jobs. These findings underscore the importance of incorporating physiotherapy into routine postpartum care for working mothers.